1956
DOI: 10.1029/tr037i004p00421
|View full text |Cite
|
Sign up to set email alerts
|

Type distributions of precipitation at selected stations in Illinois

Abstract: All the precipitation which fell during a ten‐year period at four first‐order weather stations in Illinois is classified according to its source from one of six major types of precipitation systems: (1) cold front; (2) warm front; (3) stationary front; (4) squall line; (5) warm air mass; and (6) cold air mass. The amount of precipitation and the frequency of occurrence for each of the six major types by monthly totals are presented in tabular and graphic form. Squall lines and warm air mass showers are shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1961
1961
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In the summer of 1971 the frequency of occurrence of precipitation in the moderately disturbed (squall) mode, 35%, is somewhat greater than the regional average of 25% reported by Hiser [ 1956]. In 58% of the rainfall cases associated with the undisturbed (air mass) mode an urban enhancement effect was discernible, whereas when the atmosphere evidenced synopticscale disturbances, only 25% of rainfall occurrences could be ascribed to urban effects.…”
Section: Moisture Fields Clouds and Precipitationmentioning
confidence: 78%
“…In the summer of 1971 the frequency of occurrence of precipitation in the moderately disturbed (squall) mode, 35%, is somewhat greater than the regional average of 25% reported by Hiser [ 1956]. In 58% of the rainfall cases associated with the undisturbed (air mass) mode an urban enhancement effect was discernible, whereas when the atmosphere evidenced synopticscale disturbances, only 25% of rainfall occurrences could be ascribed to urban effects.…”
Section: Moisture Fields Clouds and Precipitationmentioning
confidence: 78%
“…A previous study [12] of the average amount of precipitation associated with various synoptic types has shown that during an average year Chicago receives at least 50 per cent more cold air mass precipitation than do Moline, Springfield, and Cairo, Illinois. Furthermore, 64 per cent of this additional cold-air-mass precipitation received at Chicago occurs in the autumn and early winter.…”
Section: Transition Seasonmentioning
confidence: 93%
“…Fiering and Jackson [1971 ] recognized the existence of bimodal probability distributions (two distribution proposed in this paper is a typical one) in addition to unimodal distributions such as normal, log normal, or gamma. Bimodal or multimodal flow distributions could occur because of (1) storms of various types having their own distributions [Essenwanger, 1960;Hiser, 1956]…”
Section: Sequential Streamflow Generationmentioning
confidence: 99%